2021
DOI: 10.1038/s41598-021-89159-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcranial direct current stimulation on the psychomotor, cognitive, and motor performances of power athletes

Abstract: In sports science, transcranial direct current stimulation (tDCS) has many unknown effects on neuromuscular, psychomotor and cognitive aspects. Particularly, its impact on power performances remains poorly investigated. Eighteen healthy young males, all trained in a jumping sport (parkour) performed three experimental sessions: anodal tDCS applied either on the left dorsolateral prefrontal cortex (dlPFC, cathode in supraorbital area) or on the primary motor cortex (M1, cathode on contralateral shoulder), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 59 publications
2
60
1
Order By: Relevance
“…Synaptic plasticity in the motor cortex is associated with muscular strength and can be modified by tDCS. Some studies have shown that this technique could effectively improve training and increase performance ( Huang et al, 2019 ; Alix-Fages et al, 2020 ; Vieira et al, 2020 ; Grosprêtre et al, 2021 ). Some studies have shown that tDCS does not affect lower limb strength ( Montenegro et al, 2015 ; Maeda et al, 2017 ; Romero-Arenas et al, 2019 ); however, this may be related to differences in the chosen electrode configuration or stimulation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Synaptic plasticity in the motor cortex is associated with muscular strength and can be modified by tDCS. Some studies have shown that this technique could effectively improve training and increase performance ( Huang et al, 2019 ; Alix-Fages et al, 2020 ; Vieira et al, 2020 ; Grosprêtre et al, 2021 ). Some studies have shown that tDCS does not affect lower limb strength ( Montenegro et al, 2015 ; Maeda et al, 2017 ; Romero-Arenas et al, 2019 ); however, this may be related to differences in the chosen electrode configuration or stimulation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The program then calculated the x, y coordinates for the F3 location (according to the international 10–20 system) of DLPFC for each participant. Anodal DLPFC-tDCS was delivered using previously determined effective parameters for improving fine and gross motor performance (duration 25 min; current 2 mA; anode over left DLPFC; cathode over the contralateral supra-orbital region) [ 10 , 11 , 15 , 24 , 25 , 26 ]. Thus, the stimulation was applied to the DLPFC of the dominant hemisphere-arm system as all subjects were right-handed.…”
Section: Methodsmentioning
confidence: 99%
“…The vast majority of these studies have targeted the primary motor cortex (M1) with tDCS [ 1 , 2 , 3 ]. However, tDCS of other brain areas, such as the cerebellum [ 4 , 5 , 6 , 7 , 8 , 9 ], dorsolateral prefrontal cortex (DLPFC) [ 10 , 11 , 12 , 13 , 14 , 15 ], and supplementary motor area (SMA) [ 16 , 17 ], has also led to enhanced motor performance. The most common finding is that a 10 to 20-min tDCS application given simultaneously with motor practice improves motor skill by approximately 10% during and immediately after practice [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations